Everyday style : key pieces to sew + accessories, styling & inspiration - Jansdotter, Lotta (STC Craft, 2015)
Photographed over the course of a year in New York, Tennessee, India, and Sweden and organised by season, Jansdotter shares her sources of inspiration and how she and her friends mix and match her key pieces while working, playing, resting, and travelling.